Unraveling the mitochondrial genome of Quercus litseoides: a step towards conservation of an endangered species - Shen, Ruo-Han; Li, Yu; Yang, Liang-Hai; Zheng, Si-Si; Yan, Xu; Kozlowski, Gregor; Dai, Xi-Ling; Song, Yi-Gang (Frontiers in Plant Science, 2025)
IntroductionCompared to the large number of chloroplast genome resources in Quercus, only six mitogenomes (belonging to three sections) have been reported. To date, no mitogenome has been reported for Quercus section Cyclobalanopsis. Quercus litseoides, a representative species whose chloroplast genome has been characterized, is an endangered tree endemic to the montane cloud forests of southern China.MethodsIn this study, we assembled and annotated the mitogenome of section Cyclobalanopsis (Q. litseoides) for the first time using the HiFi reads. We examined repeat sequences, codon usage bias, RNA editing events, and chloroplast to mitochondrion DNA transfer events, and performed collinearity analysis and phylogenetic analysis with other Fagaceae species.ResultsThe mitogenome of Q. litseoides revealed a multipartite structure composed of three continuous segments with 516,686 bp in length. The genome encoded 38 protein-coding genes, 23 transfer RNA genes, and three ribosomal RNA genes. Repeat analysis uncovered diverse simple sequence repeats and interspersed sequences, and codon usage showed clear biases. Nonsynonymous sites of RNA editing showed 12 different effects on amino acids. Notably, a small amount (1.20%) of DNA sequences occurred gene transfer events between organelles in Q. litseoides. Comparative synteny analysis revealed substantial structural variation among oak mitogenomes. Quercus litseoides was closely related to Q. cerris in both the mitochondrial and chloroplast trees.DiscussionThis work fills a critical gap in mitochondrial genomic resources for Quercus section Cyclobalanopsis, and provides new insights into the structural diversity and evolutionary dynamics. It also establishes a valuable genomic foundation for phylogenetic reconstruction, adaptive evolution research, and the conservation of endangered Quercus species.